The impact of delegation of powers on the development of job performance and improvement of service provided by the Jordanian Customs Department - Al - Ta'ani, Inad Sayel (Arab Journal for Sciences and Research Publishing, 2016)
The modern administration has become a policy of facilitating procedures on references, this study focused on the opinion of decision makers, especially the owners of supervisory functions regarding the involvement of customs centers in policy-making and strategic planning, as well as expanding the powers of customs centers and giving them more of delegations. Accordingly, the researcher used all the statistical indications in order to accept or reject the null and alternative hypotheses, where the frequencies, the arithmetic averages and percentages were used for all the items used in the questionnaire. The results showed that the study sample showed a clear desire and different percentages of the need to involve centers in the formulation of policies, but the desire was greater for the sample to expand the powers granted to the customs centers. Where it was found that the staff at all levels of career, supervisors in general, as well as when the separation between the supervisors of the Department of the supervisors of the centers where all the same on the same result, where there was no significant differences at the level of significance (0,05) of null hypothesis of all options.
Keywords: delegation of authority; Development; Functionality; the service; Customs Service